2018
DOI: 10.1155/2018/6468517
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fuzzy Model Predictive Control of a Gas Turbine in the Combined Cycle Unit

Abstract: The complex characteristics of the gas turbine in a combined cycle unit have brought great difficulties in its control process. Meanwhile, the increasing emphasis on the efficiency, safety, and cleanliness of the power generation process also makes it significantly important to put forward advanced control strategies to satisfy the desired control demands of the gas turbine system. Therefore, aiming at higher control performance of the gas turbine in the gas-steam combined cycle process, a novel fuzzy model pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…These restrictions are associated with performance deterioration of the main equipment with increase of ambient temperatures. [5][6][7]. There are several steps that can be taken to remove or alleviate these restrictions.…”
Section: Methodsmentioning
confidence: 99%
“…These restrictions are associated with performance deterioration of the main equipment with increase of ambient temperatures. [5][6][7]. There are several steps that can be taken to remove or alleviate these restrictions.…”
Section: Methodsmentioning
confidence: 99%
“…For a prediction horizon N, the following cost index is minimized for the instant k [7]: J(k)=j=0N()yryfalse(k+jfalse)TQyfalse(jfalse)yry(k+j)+j=0N1δuTfalse(k+jfalse)Rfalse(jfalse)δufalse(k+jfalse).\begin{equation} \begin{split} J(k) &= \sum _{j=0}^{N}{\left(y_r-y(k+j)\right)}^T Q_{y}(j) {\left(y_r-y(k+j)\right)} \\ &\quad +\,\sum _{j=0}^{N-1} \delta u^T(k+j) R(j) \delta u(k+j). \end{split} \end{equation}…”
Section: Model Predictive Controlmentioning
confidence: 99%
“…There also (13) is zero for w = 0. Thus, stability boundary is a line defined by (12). Moreover, for w = 0 from ( 12)…”
Section: Determination Of Stable Region For Pi Type Controller Using ...mentioning
confidence: 99%
“…Hou et al proposed the fuzzy logic-based MPC method to the gas turbine model and the simulation results showed stronger disturbance rejection with higher control precision. 12 In another study, Hou et al proposed a fast MPC method for controlling a gas turbine, and it was observed that the controller has a fast settling time. 13 Kavalerov et al used adaptive control application for speed control in their natural gas turbine power plants.…”
Section: Introductionmentioning
confidence: 99%